Viscous Leptomeningeal Pseudotumoural Masses and Multiple Cranial Neuropathy – Severe Presentation of Neurosarcoidosis - Dias, Rita Ribeiro; Henriques Ferreira, Inês; Faria, Raquel (European Journal of Case Reports in Internal Medicine, 2020)
We present a case of a 56-year-old man with a history of episcleritis (left) and cluster headache (left) who had a penetrating trauma of the left eye leading to amaurosis 1 month previously. Since then, he developed multiple cranial neuropathy of the right side (V, VII, VIII, IX, X, XI and XII cranial pairs). Magnetic resonance imaging (MRI) revealed an infiltrative lesion of the base of the skull which extended to the retropharyngeal and jugular space, which progressed to multiple leptomeningeal masses extending to the clivus, despite aggressive immunosuppression. Rebiopsy of 1 meningeal mass supported the diagnosis of neurosarcoidosis. The patient finally responded to high-dose prolonged infliximab therapy, with complete remission.